Mercado de câmbio e juros no Brasil: eficiência e risco - Damiani, Barbara Hoffman (2021)
The purpose of this paper is to explore the behavior of the Brazilian market in respect of the interest rate parity conditions and the bias of the forward exchange rate, that based on the existing bibliography, would be explained primarily by a risk premium that varies over time. Focusing on the easing cycle that is being implemented in Brazil on the past few years, this paper is founded on the state-space methodology to unobserved components, that has arisen from financial engineering literature, aiming to estimate the risk premium starting from the exchange rate expectations for a future date, even if the latter cannot be observed explicitly. Using the Kalman Filter to extract a signal from the model, it was possible to obtain a proxy of the risk premium for each point in time of the period comprised between 2005 and 2020 and therefore to analyze the performance of the estimated variable of time. Based on the series of estimations, it was verified that not only the risk premium seems not to be statistically significant to explain the forecast error on the forward exchange market, but also there was a remarkable reduction of the relative relevance of such variable on the composition of the domestic short-term interest rate over time. On the other hand, the decomposition of the interest rate revealed another noteworthy component that would be attached to the high level of political and economic uncertainty inherent to Brazil: the country risk.